The classic P300 encodes a build‐to‐threshold decision variable. (28th May 2015) - Twomey, Deirdre M.; Murphy, Peter R.; Kelly, Simon P.; O'Connell, Redmond G.
Abstract The P300 component of the human event‐related potential has been the subject of intensive experimental investigation across a five‐decade period, owing to its apparent relevance to a wide range of cognitive functions and its sensitivity to numerous brain disorders, yet its exact contribution to cognition remains unresolved. Here, we carry out key analyses of the P300 elicited by transient auditory and visual targets to examine its potential role as a 'decision variable' signal that accumulates evidence to a decision bound. Consistent with the latter, we find that the P300 reaches a stereotyped amplitude immediately prior to response execution and that its rate of rise scales with target detection difficulty and accounts for trial‐to‐trial variance in RT. Computational simulations of an accumulation‐to‐bound decision process faithfully captured P300 dynamics when its parameters were set by model fits to the RT distributions. Thus, where the dominant explanatory accounts have conceived of the P300 as a unitary neural event, our data reveal it to be a dynamically evolving neural signature of decision formation. These findings place the P300 at the heart of a mechanistically principled framework for understanding decision‐making in both the typical and atypical human brain.